Avaliação da recuperação da cartilagem articular do tornozelo de ratos após aplicação de um protocolo de alongamento cíclico da musculatura posterior da perna após imobilização - Dias, Carolina Náglio Kalil (2008)
Objective: To evaluate the recovery of ankle articular cartilage of rats after applying unilateral cyclic passive muscle stretching protocol in previously hindlimb immobilization. Methods: fourty Wistar rats were divided in seven groups: C- control; I- immobilized ; RI- seven weeks recovery after immobilization; S- Stretched; RS- seven weeks recovery after stretch; IS- immobilized and stretched; ISR- immobilized-stretched and seven weeks recovery. The left ankle joint from the groups I, RI, IS and ISR were immobilized for 4 week. In the muscle stretching protocol the left ankle joint was mantained manually full dorsal flexed, 10 times for 60s with a 30s rest between each stretch, seven days a week for three weeks, to stretch the ankle plantar flexors muscle of groups IS, S, ISR and SR. The right ankle joint were free to move. After this intervention period, the rats of RI, RS, ISR groups was free to move for recovery during seven weeks. At the end of experiment, the animals were sacrified and the ankles were removed, decalcified and processed in paraffin, and stainded with Hematoxilin-Eosin. Two blinded observers evaluated morphologic changes by Mankin score. A morphometric study was carried out using a hand count of chondrocytes cells and cartilage thickness measuraments. Results: No changes in all thickness was found. The C group had the calcified cartilage bigger than the other groups. The IS group had in your treated limb more cells and clonings than the IR group, and in the non-treated more cell and clonings than the C, RI and SR groups. Conclusions: The muscle stretching after immobilization increases the number of chondrocytes and the presence of cloning, and when free movement is allowed during the recovery period from immobilization, the chondrocyte characteristics tend to return to those present before immobilization, suggesting better cellular recovery